TANTANGAN MEMBANGUN DI LAHAN RTH (KAJIAN TATA RUANG PEMBANGUNAN EDUTORIUM DI EDUPARK UMS) - Indrawati, Indrawati; Priatmono, Alfa Febela; Nurhasan, Nurhasan (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: The objective of this paper is the approval of the development of Edutorium on Edupark land which has been designated as RTH on the Surakarta City regional planning. This study was presented descriptively using content analysis methods. After being analyzed, conclusions are obtained; (a) The UMS must obtain permission from the Surakarta City Government to obtain Edupark land; (B) If UMS agrees to permit the construction of Edutorium with a simple building category and has an open land of at least 70%, it is expected that permit will be issued so on. But if Edupark has a building character is not simple and important for the environment, the management of permit for more than 4 months; (c) If no open space rules are accepted, the permit is not issued; (d) UMS has a significant opportunity to submit a request for changes in Edupark's land function through the regional planning revision process. This revision process estimates 1 to 2 years; (e) if UMS applies the green concept of public space in Edutorium buildings, it is truly one of the advantages of UMS in applying Islamic architecture. Based on the conclusions above, the following are recommended: (1) Requirement documents and development permits need to be approved before construction is carried out in the field; (2) In order to be more flexible, this year, the approved UMS immediately requested a change in Edupark from green open space to a cultivation area (yellow); and (3) Before the Edutorium is built, the fulfillment of convention needs can be done by using convention buildings around the UMS. Keywords: Green Open Space, Spatial Planning, UMSAbstrak: Tulisan ini bertujuan memahami regulasi pembangunan Edutorium di lahan Edupark yang telah ditetapkan sebagai RTH dalam RTRW Kota Surakarta. Penelitian ini dipaparkan secara deskriptif menggunakan metode analisis konten. Setelah dianalisis diperoleh kesimpulan; (a) UMS harus mendapat ijin dari Pemkot Surakarta untuk memanfaatkan lahan Edupark; (b) Jika UMS mengajukan ijin pembangunan Edutorium dengan kategori bangunan sederhana serta memiliki lahan terbuka minimal 70%, diperkirakan IMB terbit dalam waktu dekat. Namun jika Edupark memiliki karakter bangunan tidak sederhana serta berdampak penting bagi lingkungan, pengurusan IMB memakan waktu lebih dari 4 bulan; (c) Jika tidak mengikuti kaidah-kaidah RTH, dimungkinkan IMB tidak akan terbit; (d) UMS memiliki peluang cukup besar untuk mengajukan permohonan perubahan fungsi lahan Edupark melalui proses revisi RTRW. Proses revisi RTRW diperkirakan 1 hingga 2 tahun; (e) jika UMS menerapkan konsep public space yang hijau pada bangunan Edutorium, sesungguhnya merupakan salah satu kelebihan UMS dalam mengaplikasikan arsitektur Islam. Berdasarkan kesimpulan di atas, direkomendasikan beberapa hal berikut: (1) Dokumen persyaratan dan perijinan pembangunan perlu dipenuhi sebelum dilakukan pembangunan di lapangan; (2) Agar lebih fleksibel, pada tahun ini UMS sebaiknya segera mengajukan permohonan perubahan fungsi lahan Edupark dari RTH (hijau) menjadi kawasan budidaya (kuning); dan (3) Sebelum Edutorium terbangun, pemenuhan kebutuhan konvensi dapat dilakukan dengan menyewa gedung-gedung konvensi yang ada di sekitar UMS. Kata Kunci: RTH, Tata Ruang, UMS